Microstructure of arc brazed and diffusion bonded joints of stainless steel and SiC reinforced aluminum matrix composite. Issue 1 (March 2016) - Elßner, M; Weis, S; Grund, T; Wagner, G; Habisch, S; Mayr, P
Abstract: Joint interfaces of aluminum and stainless steel often exhibit intermetallics of Al-Fe, which limit the joint strength. In order to reduce these brittle phases in joints of aluminum matrix composites (AMC) and stainless steel, diffusion bonding and arc brazing are used. Due to the absence of a liquid phase, diffusion welding can reduce the formation of these critical in- termetallics. For this joining technique, the influence of surface treatments and adjusted time- temperature-surface-pressure-regimes is investigated. On the other hand, arc brazing offers the advantage to combine a localized heat input with the application of a low melting filler and was conducted using the system Al-Ag-Cu. Results of the joining tests using both approaches are described and discussed with regard to the microstructure of the joints and the interfaces.